2019
DOI: 10.1016/j.gheart.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Prognostic Models in Latin America and the Caribbean: A Systematic Review

Abstract: Background Cardiovascular prognostic models guide treatment allocation and support clinical decisions. Whether there are valid models for Latin American and Caribbean (LAC) populations is unknown. Objective This study sought to identify and critically appraise cardiovascular prognostic models developed, tested, or recalibrated in LAC populations. Methods The systematic review followed the CHARMS (CHecklist for critical Appraisal and data extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
0
16
0
3
Order By: Relevance
“…Our systematic review showed several methodological pitfalls in the development or validation of the models, especially in the analysis domain which was the main cause of high ROB. Similar to reviews assessing the quality of prognostic models for other diseases including oropharyngeal cancer, chronic lymphocytic leukemia, and chronic obstructive pulmonary disease (19,20,39,40), inadequate sample size, improper handling of missing data, and incomplete evaluation of model performance were the main problems in analysis domain and needed to be emphasized. Besides this, several other methodological details should also be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review showed several methodological pitfalls in the development or validation of the models, especially in the analysis domain which was the main cause of high ROB. Similar to reviews assessing the quality of prognostic models for other diseases including oropharyngeal cancer, chronic lymphocytic leukemia, and chronic obstructive pulmonary disease (19,20,39,40), inadequate sample size, improper handling of missing data, and incomplete evaluation of model performance were the main problems in analysis domain and needed to be emphasized. Besides this, several other methodological details should also be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this review highlights the need for researchers to adhere to the TRIPOD guidelines that were created to help authors of prognostic models write complete and transparent reports. Of note, the quality of clinical predictive models does not appear to have improved over time as previous reviews from 1996, 61 1997, 62 2001, 63 2005, 64 2011, 8 2012, 65 2016, 66 67 2017 68 –2019 69 have consistently identified suboptimal methodologies in the development of the score/predictive models especially in the domain of analysis. Poorly derived models may result in overoptimistic results and misleading performances.…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
“…The ACC/AHA risk score was calculated to measure general CVR over 10 years [ 22 ]. This score presented the best discrimination (AUC = 0.78) of general CVR in a Latin American population [ 19 ]. The population was categorized as low, borderline, intermediate, and high risk according to the ACC/AHA 2019 guidelines on the primary care of cardiovascular diseases [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different equations and scales make it possible to quantify CVR, their differences being mainly due to the specific parameters established for the calculation and population to apply [ 18 ]. The most common risk score used in the Latin American population is the Framingham and American College of Cardiology/American Heart Association (ACC/AHA) risk score, which estimates the risk of developing myocardial infarct, stroke, or peripheral artery disease at 10 years [ 19 ]. In Peru, the prevalence of high CVR is approximately 29%; however, young, middle-aged, and older adult proportions could change the prevalence of CVR in the risk calculators at 10 years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%